تعزيز دور المحاسبة في دعم غايات التنمية المستدامة - سامي سالم الحصادي (Scientific Journal of University of Benghazi, 2018)
This paper aims to illustrate the role that could be played by accounting to contribute in achieving sustainable development. To achieve the purpose of this paper, the research methodology is based on a critical review of accounting literature and literature related to the role of accounting in supporting sustainable development goals. A comprehensive literature research was conducted by using online databases of selected scientific publishers and using keywords such as sustainable development, sustainability, corporate sustainability, sustainability reporting, accounting and sustainability accounting. Based upon the literature survey, it can be said that there is a lack of defining the relationship between the sustainability concept and accounting and also potential solutions to overcome the problems which create challenges for accounting. As a result, the role of accounting in achieving the sustainable development goals is still remaining limited. Therefore, in line with sustainable development requirements, this paper recommends the proposal of developing sustainability accounting standards and put in place sustainability reporting standards. In addition, this paper recommend the credential of certified sustainability accountant that is equipped with the core knowledge of environmental engineering to handle the technical accounting problem that is related to sustainability. This paper recommends also integrating sustainability issues within accounting education curriculum and professional training programs in order to provide the basis for achieving sustainable development goals.